The Kidney Genetics Clinic: delivering precision medicine for kidney patients - Calado,Joaquim (2021)
ABSTRACT Molecular genetic testing in human traits has traditionally relied on affiliated academic facilities, been focused on specific phenotypes and supported by research funding. We report the experience of the Kidney Genetics Clinic (“consulta de Doenças Renais Hereditárias”) for the past 5 years, a period during which we have outsourced genetic testing. We evaluated the impact of molecular testing in patients’ care, but we also assessed disease‑specific imaging procedures and medicines provided. During the study period, 293 individuals were evaluated. Autosomal Dominant Polycystic Kidney Disease was the most frequent diagnosis (61.8%). In 125 patients, a genetic test was available, and for 76 of these (60.8%) a pathogenic/likely pathogenic variant was identified. Depending on the phenotype, the mutation detection rate ranged from 100% (Tuberous Sclerosis Complex) to 15.4% (Autosomal Dominant Tubulointerstitial Kidney Disease). The impact of genetic testing on patients’ diagnosis and treatments is discussed. Total kidney volume was calculated in 6 patients with Autosomal Dominant Polycystic Kidney Disease and the combined volume for selected angiomyolipoma monitored in 3 individuals with the Tuberous Sclerosis Complex. Currently, 4 patients are being treated with Everolimus/Votubia™, 3 with Eculizumab/Soliris™ and 2 with Tolvaptan/Jinarc™. Our results demonstrate the feasibility of genetic molecular testing in a clinical setting while relying on outsourced sites for gene testing. We emphasize that it was only because the Kidney Genetics Clinic was given the opportunity to look after several patients affected by the same specific orphan or rare diseases (cohort enrichment) that we were able to improve diagnostic skills and deliver personalized medicines.